KEDUDUKAN DAN TUGAS KEPALA DESA SEBAGAI HAKIM PERDAMAIAN DESA DI DESA PAKRAMAN TAMAN-TANDA KECAMATAN BATURITI KABUPATEN TABANAN - Anom Rai Putra, Dewa Nyoman; Wita, I Nyoman (Kertha Desa; Vol. 02, No. 02, Mei 2014)
In this period there are most of conflict problem usually to turn up in the sociallife. As like the problem of economy,politic,and etc. That happened would to appearimportance,it is usually we are found in social life. It's specialy in the baturtiti village,tabanan regency. To do the finished of matter we are seen usually it's done in front ofhead social life. We just call them by the justice of peace in village. The head of villageas the justice of peace, there are the task from pakraman village header. To done andbuilt up the peaceful of matters have been happen in the social life. That recognize inthe region system. How the position and task of header village as the justice of peaceand how to do. By the punctual of yuridis,empiris and how to done the problem,thatonly one way to get the finished as like to share the problem with other heads andpeople of the village and take the solutions. As be the law norm that happened in sociallife to get the peace in village.
Keywords: position, duties, village justice of the peace